Exploring expert figures in alien-related UFO conspiracy theories - Maria Lipińska; Nina Kotula; Dariusz Jemielniak (Humanities & Social Sciences Communications)
Abstract This study investigates expert figures’ roles in alien-related UFO conspiracy theories, focusing on their impact on public perception through social media analysis. Utilizing a blend of content and trend analysis, we examine the invocation of scientific authority in UFO conspiracy narratives, identifying a reliance on expert endorsement to legitimize claims about extraterrestrial activity and government secrecy. Findings highlight a common use of expert figures, often without empirical backing, to bolster conspiracy theories.The research reveals the challenge of distinguishing credible information from conspiracy in a landscape where expert authority is easily co-opted. This underscores the importance of scientific literacy and critical thinking in combating disinformation. The study’s implications extend to educational and policy measures aimed at fostering a skeptical and informed public debate on controversial topics. By exploring the dynamics between authority, belief, and disinformation, this work contributes to understanding the mechanisms behind the spread of conspiracy theories and the complex role of expertise in shaping public discourse in the digital age.